Health and Safety of a Work Environment in an Islamic Perspective - Ernyasih Ernyasih; Dihartawan Dihartawan; Aragar Putri; Irna Hasanah; Widya Rizki Ariandini (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
Work environment safety and health is a program designed as an effort to prevent occupational accidents and diseases by identifying, controlling and monitoring potential hazards in the work environment. In working, every Muslim must pay attention to occupational health and safety, because accidents can occur due to various causes. Islam teaches its people to work and work safely and safely recommended by the Prophet Muhammad. The K3 relationship with Islam is the same as reminding us to always behave in a safe and healthy manner at work wherever we work. Efforts are made to minimize, eliminate and control the potential dangers that exist, which can endanger oneself and others. In Islam, occupational safety and health is doing a job in the best possible way and prioritizing maintaining safety and health, because Islam highly respects safety for its adherents. Islam in the Al-Qur'an and hadiths prohibits people from causing damage, let alone the damage to the environment, to oneself Allah forbids it.